23.2k views
3 votes
The sum of two polynomials is –yz2 - 322 – 4y + 4. If one of the polynomials is y - 4yz2 - 3, what is the other polynomial? 0 -2yz? – 4y + 7 01-2yz? – 3y + 1 0 -5yz2 + 3z2 – 3y + 1 03yz2 - 3z2 – 5y +7 Done Intro ok

.


1 Answer

5 votes

Answer:

3yz² - 3z² - 5y + 7

Explanation:

Sum of two polynomials = –yz² - 3z² – 4y + 4

One of the polynomial = y - 4yz²- 3

Find the other polynomial

The other polynomial = sum of the polynomials - one of the polynomial

= –yz² - 3z² – 4y + 4 - (y - 4yz² - 3)

= –yz² - 3z² – 4y + 4 - y + 4yz² + 3

= -yz² + 4yz² - 3z² - 4y - y + 4 + 3

= 3yz² - 3z² - 5y + 7

A. 0 -2yz?

B. – 4y + 7 01 - 2yz

C. – 3y + 1 0 -5yz² + 3z² – 3y + 1 D. 3yz² - 3z² – 5y + 7

User Helper
by
4.2k points